Roles of RNA-binding proteins in immune diseases and cancer. (November 2022) - Hashimoto, Shigeru; Kishimoto, Tadamitsu
Abstract: Genetic information that is transcribed from DNA to mRNA, and then translated from mRNA to protein, is regulated by complex and sophisticated post-transcriptional mechanisms. Recently, it has become clear that mRNA degradation not only acts to remove unnecessary mRNA, but is also closely associated with the regulation of translation initiation, and is essential for maintaining cellular homeostasis. Various RNA-binding proteins (RBPs) have been reported to play central roles in the mechanisms of mRNA stability and translation initiation through various signal transduction pathways, and to modulate gene expression faster than the transcription process via post-transcriptional modifications in response to intracellular and extracellular stimuli, without de novo protein synthesis. On the other hand, inflammation is necessary for the elimination of pathogens associated with infection, and is tightly controlled to avoid the overexpression of inflammatory cytokines, such as interleukin 6 (IL-6) and tumor necrosis factor (TNF). It is increasingly becoming clear that RBPs play important roles in the post-transcriptional regulation of these immune responses. Furthermore, it has been shown that the aberrant regulation of RBPs leads to chronic inflammation and autoimmune diseases. Although it has been recognized since the time of Rudolf Virchow in the 19th century that cancer-associated inflammation contributes to tumor onset and progression, involvement of the disruption of the balance between anti-tumor immunity via the immune surveillance system and pro-tumor immunity by cancer-associated inflammation in the malignant transformation of cancer remains elusive. Recently, the dysregulated expression and activation of representative RBPs involved in regulation of the production of pro-inflammatory cytokines have been shown to be involved in tumor progression. In this review, we summarize the recent progress in our understanding of the functional roles of these RBPs in several types of immune responses, and the involvement of RBP dysregulation in the pathogenesis of immune diseases and cancer, and discuss possible therapeutic strategies against cancer by targeting RBPs, coupled with immunotherapy.